Nations of entrepreneurs: A social capital perspective - Kwon, Seok-Woo; Arenius, Pia (Journal of Business Venturing, 2010)
This research examined the effects of social capital on entrepreneurial opportunity perception and weak tie investment using individual-level data from the Global Entrepreneurship Monitor linked with national-level data on social capital. Consistent with a social capital perspective, this study found that a resident of a country with higher generalized trust and breadth of formal organizational memberships was more likely to perceive entrepreneurial opportunities. A resident of a country with higher generalized trust was also more likely to invest in an entrepreneur with whom he or she had a weak personal tie than was a resident of a country with lesser generalized trust.